Enablers and barriers of clinical trial participation in adult patients from minority ethnic groups: a systematic review - Germán Andrés Alarcón Garavito; Katie Gilchrist; Coziana Ciurtin; Sanjay Khanna; Pinkie Chambers; Nick McNally; Edward Merivale; Edi Carr; Rosamund Yu; Cecilia Vindrola-Padros (Trials)
Abstract Background Clinical trials are essential to the development of healthcare innovations that advance life expectancy and improve quality of life. However, there exists a pronounced disparity in ethnic representation among trial participants. This imbalance, particularly in relation to minority ethnic groups, can lead to a limited understanding of how therapies affect diverse populations. The present systematic literature review (SLR) aims to identify the factors that both hinder and facilitate the participation of minority ethnic groups in clinical trials. Methods This review involved a systematic search of keywords across four databases: Web of Science, PubMed, CINAHL Plus and The Cochrane Library. The review was not restricted by language or study site; however, the date of publication was limited between 1st January 2017 and 1st October 2022. Studies discussing or outlining the involvement of minority ethnic groups in clinical trials, and those outlining inclusive recruitment and participation procedures were targeted. Results A total of 43 articles were included in the review. Of these, 36 articles were from the United States (US), 20 articles reported on oncology trials and 39 articles reported information from the patient’s perspective. Reported barriers included a lack of researchers from minority ethnic groups implementing and conducting clinical research, inadequate funding for clinical trial efforts in geographical areas serving minority populations and a lack of awareness and education among research staff regarding which underrepresented groups to target for recruitment and the strategies to employ in reaching out to them. Several recommendations were suggested by the articles included in the review to address these barriers. Prominently, the use of patient navigators or community liaison roles was highly recommended as a way of supporting patients through the research recruitment process. The articles also highlighted the benefits of translating study materials and interventions into multiple languages and actively involving diverse communities in the development of health education materials. Lastly, leveraging technologies to address socioeconomic barriers, such as the use of virtual approaches to avoid lengthy travel, may also help to improve diversity in trials. Conclusions Ensuring representation of minority ethnic groups in clinical trials is critical to developing therapies with generalisable efficacies. While progress has been made in enhancing outreach of wider racial groups and fortifying educational resources, there remains a pressing need to delve deeper into the obstacles impeding the recruitment of a diverse participant base, particularly in regions outside the US, where relevant studies are scarce. Registration The review protocol was registered on PROSPERO (CRD42022368106) (1).